An Efficient Nickel‐Catalyzed Asymmetric Oxazole‐Forming Ugi‐Type Reaction for the Synthesis of Chiral Aryl‐Substituted THIQ Rings. Issue 29 (4th May 2017) - Li, Dan; Yang, Dongxu; Wang, Linqing; Liu, Xihong; Wang, Kezhou; Wang, Jie; Wang, Pengxin; Liu, Yuyang; Zhu, Haiyong; Wang, Rui
Abstract: A nickel‐catalyzed asymmetric oxazole‐forming Ugi reaction of C, N‐cyclic azomethine imines and isonitriles is disclosed. The reported protocol proceeds smoothly, and gives the corresponding adducts, which contain two important pharmaceutically active ring‐systems (tetrahydroquinoline and oxazole rings), in good yields and excellent enantioselectivities by employing an easily accessible chiral diamine as a ligand. This simple and efficient strategy provides easy access to a series of C1‐substituted aryl tetrahydroisoquinolines. Abstract : A unique oxazole‐forming Ugi type reaction is reported. The reaction employs a simple and efficient nickel(II) catalyst with an easily accessed chiral diamine ligand, and combines two types of functional rings into a chiral skeleton with high enantioselectivity. The product rings are important moieties within pharmaceutical products.